2012
DOI: 10.1016/j.jcp.2012.06.022
|View full text |Cite
|
Sign up to set email alerts
|

Preserving energy resp. dissipation in numerical PDEs using the “Average Vector Field” method

Abstract: a b s t r a c tWe give a systematic method for discretizing Hamiltonian partial differential equations (PDEs) with constant symplectic structure, while preserving their energy exactly. The same method, applied to PDEs with constant dissipative structure, also preserves the correct monotonic decrease of energy. The method is illustrated by many examples. In the Hamiltonian case these include: the sine-Gordon, Korteweg-de Vries, nonlinear Schrödinger, (linear) time-dependent Schrödinger, and Maxwell equations. I… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
205
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 269 publications
(205 citation statements)
references
References 32 publications
0
205
0
Order By: Relevance
“…For j = N , we use the periodic extension to define (Q θ ω) + N +1/2 , in order to be consistent with the numerical flux defined in (7).…”
Section: The Global Projectionmentioning
confidence: 99%
See 2 more Smart Citations
“…For j = N , we use the periodic extension to define (Q θ ω) + N +1/2 , in order to be consistent with the numerical flux defined in (7).…”
Section: The Global Projectionmentioning
confidence: 99%
“…Let (u h , p h , φ h ) be obtained from (6) with the choice of fluxes (7). Let θ ∈ [0, 1] be such that both Q θ and Q 1−θ are uniquely defined, then the following inequality holds for all t > 0.…”
Section: Lemma 44 Let (U P φ) Be the Exact Solution Of The System mentioning
confidence: 99%
See 1 more Smart Citation
“…The piano sounds are computed by integrating a Hamiltonian partial differential equation (PDE) model describing the oscillations of the string and an ordinary differential equation (ODE) model describing the dynamics of the hammer. The procedure has its basis on the semi-discretization method by Celledoni et al [13], which semi-discretizes the PDE to a system of ODEs while preserving the Hamiltonian structure. This method allows the application of geometric integrators, which are numerical integrators with excellent quality for Hamiltonian ODEs.…”
Section: Introductionmentioning
confidence: 99%
“…Using the B-series, it can shown that the AVF method for canonical and non-canonical Hamiltonian systems is conjugate to symplectic or Poisson integrators [6,7]. Application of the AVF method for various nonlinear evolutionary partial differential equation was given in [8].…”
Section: Introductionmentioning
confidence: 99%